CCR2 Mediates Chronic LPS-Induced Pulmonary Inflammation and Hypoalveolarization in a Murine Model of Bronchopulmonary Dysplasia - Cui, Tracy X.; Brady, Alexander E.; Fulton, Christina T.; Zhang, Ying-Jian; Rosenbloom, Liza M.; Goldsmith, Adam M.; Moore, Bethany B.; Popova, Antonia P. (Frontiers in Immunology, 2020)
The histopathology of BPD includes hypoalveolarization and interstitial thickening due to abnormal myofibroblast accumulation. Chorioamnionitis and sepsis are major risk factors for BPD development. The cellular mechanisms leading to these lung structural abnormalities are poorly understood. We used an animal model with repeated LPS administration into the airways of immature mice to simulate prolonged airway exposure to gram-negative bacteria, focusing on the role of CCR2+ exudative macrophages (ExMf). Repetitive LPS exposure of immature mice induced persistent hypoalveolarization observed at 4 and 18 days after the last LPS administration. LPS upregulated the expression of lung pro-inflammatory cytokines (TNF-α, IL-17a, IL-6, IL-1β) and chemokines (CCL2, CCL7, CXCL1 and CXCL2), while the expression of genes involved in lung alveolar and mesenchymal cell development (PDGFR-α, FGF7, FGF10 and SPRY1) was decreased. LPS induced recruitment of ExMf, including CCR2+ ExMf, as well as other myeloid cells like DCs and neutrophils. Lungs of LPS-exposed CCR2-/- mice showed preserved alveolar structure and normal patterns of α-actin and PDGFRα expression at the tips of the secondary alveolar crests. Compared to wild type mice, a significantly lower number of ExMf, including TNF-α+ ExMf were recruited to the lungs of CCR2-/- mice following repetitive LPS exposure. Further, pharmacological inhibition of TLR4 with TAK-242 also blocked the effect of LPS on alveolarization, α-SMA and PDGFRα expression. TNF-α and IL-17a induced α-smooth muscle actin expression in the distal airspaces of E16 fetal mouse lung explants. In human preterm lung mesenchymal stromal cells, TNF-α reduced mRNA and protein expression of PDGFR-α and decreased mRNA expression of WNT2, FOXF2 and SPRY1. Collectively, our findings demonstrate that in immature mice repetitive LPS exposure, through TLR4 signaling increases lung inflammation and impairs lung alveolar growth in a CCR2-dependent manner.